Time as a Postmodern Game in the Novel Concert for the Reviews by Helena Shvarts: Gogol, Dovlatov and Co. .......... 545 - Vorontsova, Kristina (Czas w kulturze rosyjskiej, 2019)
TIME AS A POSTMODERN GAME IN THE NOVEL CONCERT FOR THE REVIEWS BY HELENA SHVARTS: GOGOL, DOVLATOV AND CO.The postmodern concept of time and its connections with literary creative work and art in general are investigated in this paper on a material of a novel Concert for the Reviews by Helena Shvarts. The author, who was best known for her mystical and religious poems during the period of Leningrad underground in 70-s, in 2007 wrote a vivid example of so called “prose of a poet” where different issues of Time (this word and its derivations appear more than 23 times in the text) were analysed as well as Linear Time as a commonplace principle was destructed. It became possible due to intertextuality, a big variety of quotations and self-quotations, allusions and participations of real historical subjects like Gogol, Blok, Poe etc. in the plot. Furthermore, the central story line of Semerkin and his employer, Soviet writer Balamutova, is not only an ironical and obvious allusion on Sergei Dovlatov and Vera Panova’s relationship, but also a typical image of the whole Soviet generation of 70-s that was not able to write because of the ideology and censorship. Moreover, the typical representor of future postmodern and underground consciousness was sent to 1953 by author’s will and according to her conception about talented men of letters who are not able to exist in their normal Time and hence belong to the Eternity.